Incoming Veterinary Students’ Perspectives on Animal Welfare: A Qualitative Study - Dolby, Nadine E. (Journal of applied animal ethics research, 2020)
Abstract Animal welfare is an increasingly important component of veterinary medicine. While the AVMA Model Animal Welfare Curriculum is not required, there is growing research that examines veterinary students’ understanding of animal welfare and moral and ethical responsibility to animals. However, there is limited research that investigates incoming veterinary students’ perspectives on animal welfare: a significant pedagogical gap, as successful curriculum interventions take into account students’ pre-existing experiences. This study investigates this gap in the literature through a qualitative, interview-based study of twenty incoming veterinary students at an accredited veterinary college. Four themes are identified in the data: formative childhood experiences; pre-professional experiences in the field; public conversations in the media/ social media; and academic definitions memorized for admission interviews. In conclusion, I draw on the field of narrative medicine to discuss how students’ stories are important to understanding the curriculum and pedagogy of animal welfare in veterinary education.